2016
DOI: 10.7763/ijssh.2016.v6.704
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Child Labour as a Form of Child Abuse in Malaysia

Abstract: Abstract-International Labour Organization (ILO)estimates that there are about 250 million economically active children worldwide. In Malaysia, although the Children and Young Persons Act (Employment) 1966 prohibits the children to be employed, previous studies proved that there are high rate of working children in certain states in Malaysia. It is believed that thousands of working children in Malaysia to be in an environment which is potentially harmful to their physical, mental, emotional, and social develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is in line with a review study by Bywaters et al (2016) who reported associations between poverty and CM. Similarly, Nik Ahmad Kamal Nik et al (2016) found that working children in Malaysia experienced physical, emotional, and sexual abuse by their employers. Our results are also confirmed by a children's opinion poll, which found that one quarter of all working children in Bangladesh were physically punished at their working places (Unicef, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…This is in line with a review study by Bywaters et al (2016) who reported associations between poverty and CM. Similarly, Nik Ahmad Kamal Nik et al (2016) found that working children in Malaysia experienced physical, emotional, and sexual abuse by their employers. Our results are also confirmed by a children's opinion poll, which found that one quarter of all working children in Bangladesh were physically punished at their working places (Unicef, 2008).…”
Section: Discussionmentioning
confidence: 98%